Recent expansion of Daphnia across Beringia, 2001-2011 ... - Taylor, Derek (NSF Arctic Data Center, 2017)
Daphnia pulex is quickly becoming an attractive model species in the field of ecological genomics due to the recent release of its complete genome sequence, a wide variety of new genomic resources, and a rich history of ecological data. Sequences of the mitochondrial NADH dehydrogenase subunit 5 and cytochrome c oxidase subunit 1 genes were used to assess the global phylogeography of this species, and to further elucidate its phylogenetic relationship to other members of the Daphnia pulex species complex. Using both newly acquired and previously published data, we analyzed 398 individuals from collections spanning five continents. Eleven strongly supported lineages were found within the D. pulex complex, and one lineage in particular, panarctic D. pulex, has very little phylogeographical structure and a near worldwide distribution. Mismatch distribution, haplotype network, and population genetic analyses are compatible with a North American origin for this lineage and subsequent spatial expansion in the Late ...